Disseminated mycosis in a patient with yellow fever - Gustavo Vieira Rodrigues Maciela; Marcelo Combat de Faria Tavares; Leonardo Soares Pereira; Guilherme Lima Castro Silva; Neimy Ramos de Oliveira; Eduardo Paulino Júnior; Marcelo Antonio Pascoal-Xavier (University of São Paulo, 2018)
Disseminated mycosis (DM)-with cardiac involvement and shock-is an unexpected and severe opportunistic infection in patients with yellow fever. DM can mimic bacterial sepsis and should be considered in the differential diagnosis of causes of systemic inflammatory response syndrome in this group of patients, especially in areas where an outbreak of yellow fever is ongoing. We report the case of a 53-year-old male patient who presented to the emergency department with fever, myalgia, headache, and low back pain. The laboratory investigation revealed a positive molecular test for yellow fever, hepatic injury, and renal failure. During hospitalization, the patient developed hepatic encephalopathy, ascending leukocytosis, and ascites, with signs consistent with peritonitis. On the 11th day of hospitalization, the patient developed atrioventricular block, shock and died. At autopsy, angioinvasive mycosis was evidenced mainly in the heart, lungs, kidneys, and adrenals.